Searching the past in the future: joining cuneiform tablet fragments in virtual collections - Gehlken, Erlend; Collins, Tim; Woolley, Sandra I.; Ch’ng, Eugene (2017)
Joining cuneiform tablet fragments are separated within and between collections worldwide. In previous work of the Virtual Cuneiform Tablet Reconstruction Project [VCTR, 2018], automated joins were achieved for virtual 3D Ur and Uruk fragments held within the same collections. By virtue of this fact, these physical fragments were in close proximity to each other and, therefore, manual verification of each join could be readily achieved. Now, for the first time, a long-distance join is reported between cuneiform tablet fragments separated by 1000 km.